2019
DOI: 10.1097/mpa.0000000000001249
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interactions With Cancer-Associated Fibroblasts Lead to Enhanced Pancreatic Cancer Stem Cell Function

Abstract: Objective: Cancer-associated fibroblasts (CAFs) play an important role in the progression of pancreatic ductal adenocarcinoma (PDAC) by promoting tumor cell migration and drug resistance. We determined the impact of CAFs on PDAC cancer stem cells (CSCs).Methods: Fibroblast cell lines from patients' tumors were co-cultured with PDAC cells and examined for clonogenic growth and self-renewal using colony forming assays and migration in vitro. Changes in the frequency of CSCs was determined by flow cytometry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…For example, Kolev et al showed that administration of VS-4718 or VS-6063, two potent FAK inhibitors, to mice bearing TNBC xenografts significantly reduced the CSC population [ 86 ]. Recently, it was shown in PDAC that FAK activation promotes PaCSCs, and short hairpin RNAs against FAK or a small-molecule FAK inhibitor can inhibit PaCSC clonogenic growth [ 87 ]. Thus, the inhibition observed in the PaCSC population in this study with DAS and PP2 may very well be due to the SRC /FAK axis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kolev et al showed that administration of VS-4718 or VS-6063, two potent FAK inhibitors, to mice bearing TNBC xenografts significantly reduced the CSC population [ 86 ]. Recently, it was shown in PDAC that FAK activation promotes PaCSCs, and short hairpin RNAs against FAK or a small-molecule FAK inhibitor can inhibit PaCSC clonogenic growth [ 87 ]. Thus, the inhibition observed in the PaCSC population in this study with DAS and PP2 may very well be due to the SRC /FAK axis.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs have been implicated in promoting stemness in adjacent tumour cells via the secretion of inflammatory cytokines in several tumour types [23,[63][64][65][66][67][68][69], including PDAC [70,71]. More recently, it was reported that certain subpopulations of CAFs specifically regulate stemness in lung and breast tumour cells, thus conferring chemoresistance [72] ( Figure 1E).…”
Section: Caf Heterogeneity In Promoting Stemnessmentioning
confidence: 99%
“…Previously described pathways involved in CAF activation include sonic hedgehog, TGF-beta, IL-1, IL-6, and IL-10 [29,43,[55][56][57][58][59]. CAFs are also activated by growth factors and cytokines such as CCL2, PDGF, hepatocyte growth factor, and fibroblast growth factor (FGF) [60]. Once activated CAFs develop a contractile and secretory function, secreting many of the factors known to be further involved in their activation including IL-1 and IL-6 [56].…”
Section: Pdac Caf Heterogeneitymentioning
confidence: 99%